The Christianization of the Peruvian indigenous [1969] - Marzal, Manuel (2007)
I present in these pages the most important points of the Christianization of the Peruvian indigenous. I limit myself to the evangelizing task during the 16th century, and only on some points —such as the fight against idolatry— I extend well into the 17th century. By Christianization I understand the reception of baptism and a series of values, rites and norms that can be considered Christian.